Facilitators and barriers to self-management of nursing home residents: perspectives of health-care professionals in Korean nursing homes - Park YH (Dove Medical Press, 2015)
Yeon-Hwan Park,1,2 Hwal Lan Bang,2,3 Ga Hye Kim,1 Ji Yeon Ha1 1College of Nursing, Seoul National University, Seoul, Korea; 2The Research Institute of Nursing Science, Seoul National University, Seoul, Korea; 3Department of Nursing Science, College of Industry, Sangmyung University, Cheonan, Korea Purpose: To explore facilitators and barriers to self-management from the viewpoint of staff taking care of nursing home (NH) residents with chronic diseases in South Korea. Patients and methods: A qualitative content analysis was done using the focus group interview method. A total of 23 health-care professionals (16 registered nurses and 7 social workers) were interviewed from three urban NHs, each with more than 100 beds. Results: Five facilitators were identified: grouping the residents; the resident’s awareness of his/her current health status; the willingness of residents to engage in self-management; residence in the facility; and support from the staff. Additionally, seven barriers were identified: deterioration of the resident’s health; the dependency expectations of the resident; hesitation in asking for help; difference in expectations between the staff and the resident’s family; insufficient staffing and time; lack of standardized guidelines; and conservative tendencies of the staff due to rigid policies. Conclusion: The findings of this study can help health-care professionals recognize the factors that influence self-management and provide direction for registered nurses and other health professionals involved in supporting self-management programs for NH residents. Keywords: self-management, aged, focus groups, long-term care